Penilaian Jasa Ekosistem Mangrove di Teluk Blanakan Kabupaten Subang - Martini Dwi Indrayanti; Achmad Fahrudin; Isdradjad Setiobudiandi (Institut Pertanian Bogor, 2015)
Mangrove is one of the natural resource that has an important role in maintaining the balance between land-based and aquatic ecosystems. Therefore the ecosystems are placed as one of the life-supporting ecosystems which is needed to be preserved. This study was held in Blanakan Bay with objectives were: 1) To describe the covered area of mangrove ecosystem; and 2) To calculate the value of mangrove ecosystem services. Mangrove covered area was obtained through satellite image analysis while ecosystem services was anlyzed by economic valuation method. Economic valuation for mangrove ecosystem services is an important variable in coastal management. The result showed that mangrove covered area was decreasing by 5% per year during the period of 2005-2012 while the value of the ecosystem services in the study area was Rp3.815.790.110,97/year.